(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2025)
Hyperlipidemia, characterized by elevated levels of various lipid fractions in plasma, is a significant risk factor for cardiac conditions such coronary artery syndrome, stroke, and cardiac arrest. Traditional treatments often involve synthetic hypolipidemic drugs (such as statins, fibrates, and niacin) which can have adverse effects (like muscle pain, liver damage, and digestive problems). Consequently, there is a growing interest in natural alternatives for managing hyperlipidemia. Misidentifying or adulterating plant material can compromise the effectiveness of medicinal plants. Evaluating the pharmacognostic parameters is essential in ensuring the authenticity and quality of these plants. Fraxinus micrantha, a plant used traditionally in the Himalayas for its therapeutic properties, was investigated for its potential hypolipidemic effects. The study involved collecting and analyzing the leaves of Fraxinus micrantha for its phytochemical composition and hypolipidemic effects in a Wistar rat model produced by diet rich in fat. A total of six male Albino Wistar rats of weight 190 ± 15 g each were used to construct test, atorvastatin standard, and high-fat diet (HFD) control groups. Organoleptic, microscopic, and physicochemical evaluations confirmed the plant's quality and composition. The extracts at 200 and 400 mg per kilogram of body weight orally were assessed for their impact on lipid profiles, showing that both Fraxinus micrantha aqueous (FMAQ) and methanol extracts (FME) significantly reduced serum cholesterol, triglycerides, and LDL levels while increasing HDL, with FME showing superior efficacy compared to FMAQ. The study highlights the potential of Fraxinus micrantha as a natural hypolipidemic agent, offering a promising alternative to synthetic drugs.